Non-pigmented villonodular synovitis of knee joint in a 11-year-old boy on long term steroids: a case report - K. S. Rao, Shreekantha; Gowda, K. Nikil (International Journal of Research in Orthopaedics, 2022)
Pigmented villonodular synovitis (PVNS) is a rare condition, commonly affecting the knee joint and hip joint. It is seldomly seen in pediatric age group. Aetiology is unknown. Magnetic resonance imaging (MRI) is the imaging modality of choice. Managed by surgical resection of the synovium performed with an open, arthroscopic or combined approach. Post-operative adjuvant external beam radiotherapy have reduced recurrence rate. In this case report we are going to present a rare case of eleven-year-old boy on long term steroid intake, who presented with a history of pain and swelling of right knee joint with restriction of range of movements. MRI suggested extensive villonodular synovitis of knee joint. Diagnostic arthroscopy showed extensive villonodular synovitis of suprapatellar pouch, medial gutter, lateral gutter, intercruciate space, posterior-medial and posterior-lateral compartments and villi had atypical yellow fatty appearance. Extensive arthroscopic synovectomy was done and histopathology showed chronic synovitis. Post-operatively pain and swelling reduced and range of movements improved. Arthroscopic synovectomy is the most effective line of management for villonodular synovitis.